Praktik keagamaan dan tradisi lokal selama Idul fitri: Takbir keliling, nyekar dan megengan di Desa Tritunggal Kecamatan Babat Kabupaten Lamongan - HANUM, NAJWA ADIBAH (Maliki Interdisciplinary Journal, 2024)
This research aims to investigate the tradition of celebrating Eid al-Fitr in Tritunggal village. The specific objectives of this research are as follows: Documenting Local Traditions Gathering information about the unique rituals, activities, and traditions associated with the Eid celebration in Tritunggal Village, including prior preparations, religious processions, and celebrations of the local community. The method used is Observation, which is a data collection activity based on direct observation to Tritunggal village, especially the concrete hamlet with a focus on observing the activities carried out in celebrating Eid al-Fitr. The results showed that in celebrating the Eid celebration there is a tradition that is still preserved today. Eid al-Fitr is a special moment for Muslims. This moment is a moment awaited by Muslims after fasting. Many activities are carried out in welcoming Eid al-Fitr including nyekar, megengan, and travelling takbir.